The Design Space of Type Checkers for XML Transformation Languages - Møller, Anders; Schwartzbach, Michael I. (BRICS Report Series, 2004)
We survey work on statically type checking XML transformations, covering a wide range of notations and ambitions. The concept of type may vary from idealizations of DTD to full-blown XML Schema or even more expressive formalisms. The notion of transformation may vary from clean and simple transductions to domain-specific languages or integration of XML in general-purpose programming languages. Type annotations can be either explicit or implicit, and type checking ranges from exact decidability to pragmatic approximations. We characterize and evaluate existing tools in this design space, including a recent result of the authors providing practical type checking of full unannotated XSLT 1.0 stylesheets given general DTDs that describe the input and output languages.